REDUPLICATION IN THE NOVEL “BAXITSIZLAR” BY TULEPBERGEN KAIPBERGENOV - Kdirbaeva, B.K. (SCIENCE and SOCIETY, 2025)
This study examines the reduplicative words found in Tulepbergen Kaipbergenov’s epic historical novel “Baxıtsızlar” (“The Miserables”). The novel exhibits five types of reduplication: full, echo, intensifying, ablaut, and synonymous. These reduplicative constructions exhibit various semantic and functional features. It should be noted that reduplication is often found in literary works in Karakalpak. They give a special expressiveness to the narrative.